Central Bank Policies and Climate Change. Where Do We Stand? - Uwe Vollmer (Credit and Capital Markets – Kredit und Kapital, 2022)
The article reviews the literature on the relationship between climate change and central bank policies. Central banks conduct monetary policy and are responsible for macroprudential supervision. The article focuses on the consequences of transition and physical risks for financial stability and price stability. It also asks what role central banks can play in slowing climate change and what implications climate change has for the future strategy and for the monetary policy framework of the Eurosystem.
Keywords: E52; E58; Q54; 330; Physical risk; transition risk; monetary policy; macroprudential policy; green~QE